Bilateral Lateral Rectus Palsy Following Dengue Fever: A Rare Case Report - Manisha Meena; Rajesh Kumar Meena; Arvind Chauhan (Delhi Journal of Ophthalmology)
A 25 year old male was diagnosed with bilateral lateral rectus palsy following dengue fever. The patient was managed accordingly, and full ocular recovery was observed. However, abducens nerve involvement, manifesting with lateral rectus palsy following is so rare. Cases with unilateral lateral rectus palsy with dengue has been documented but bilateral lateral rectus palsy following dengue fever were never documented in previous literature.